2,3,4,6-Tetra-O-acetyl-β-d-galactopyranosyl 2-(2,4-dichloroanilino)-4,4-dimethyl-6-oxocyclohex-1-enecarbodithioate - El Ashry, El Sayed H. (International Union of Crystallography, 2009)
The cyclohexene ring in the title compound, C(29)H(33)Cl(2)NO(10)S(2), adopts an envelope conformation, with the C atom bearing the two methyl groups representing the flap. This atom deviates by 0.63 (1) Å from the plane through the other five ring atoms (r.m.s. deviation = 0.11 Å). The molecular conformation is stabilized by an intramolecular N—H⋯S hydrogen bond. The crystal studied was a non-merohedral twin, with a minor twin component of 29%.